Method for producing R-T-B system sintered magnet

By adjusting the chemical composition and thermal treatment conditions of the R -T -B -based sintering magnetic raw material, the HCJ improvement has been solved, and the problem of BR decreased, realizing the dual improvement of high HCJ and BR, and avoiding the dependence of DY that is unstable.

CN111724985BActive Publication Date: 2025-01-24PROTERIAL LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202010199549.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-09-25
Filing Date
2020-03-20
Publication Date
2025-01-24
Estimated Expiration
2040-03-20

AI Technical Summary

Technical Problem

When the prior art increases the coercive force HcJ of the R-T-B system sintered magnet, the residual magnetic flux density Br is often reduced, and due to the unstable supply of Dy, price fluctuations are difficult to avoid.

Method used

Adjust the composition of chemical composition in the raw material of the R -T -B -based sintering magnet, increase the GA content, and perform hot treatment of more than 10 seconds at 400 ° C and less than 600 ° C. reduce.

Benefits of technology

It is possible to improve the HcJ and Br of RT-B series sintered magnets without using the heavy rare earth element Dy, ensuring stable improvement in magnetic properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0002418891620000111
    Figure BDA0002418891620000111
  • Figure BDA0002418891620000112
    Figure BDA0002418891620000112
Patent Text Reader

Abstract

The present invention provides a method for suppressing Dy content and having high B r and high H cJ A method for manufacturing an R-T-B system sintered magnet. The method for manufacturing an R-T-B system sintered magnet comprises: a step of preparing an R-T-B system sintered magnet raw material containing at least R, B, Ga and T, wherein R: 27.0 mass % to 35.0 mass %, B: 0.80 mass % to 0.93 mass %, Ga: 0.15 mass % to 1.0 mass %, T: 61.5 mass % to 70.0 mass % (T is Fe or Fe and Co, and 90 mass % or more of T is Fe), and the R-T-B system sintered magnet raw material satisfies the formula (1): 14[B] / 10.8<[T] / 55.85; and a heat treatment step of heat treating the R-T-B system sintered magnet raw material by maintaining the heat treatment temperature of 400°C to 600°C for a holding time of 10 seconds or more and less than 30 minutes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for manufacturing an R-T-B system sintered magnet. Background Art

[0002] R2T 14 R-T-B sintered magnets (R is a rare earth element containing at least one selected from Nd, Pr and Ce; T is Fe or Fe and Co, and more than 90 mass% of T is Fe) with B-type compounds as the main phase are well-known as the highest performance magnets among permanent magnets and are used in various motors for hybrid vehicles, electric vehicles and home appliances.

[0003] The coercivity H of R-T-B sintered magnet at high temperature cJ (hereinafter sometimes referred to as “H cJ ”) decreases, causing irreversible thermal demagnetization. Therefore, when used in hybrid vehicles and electric vehicles, it is necessary to maintain a high H even at high temperatures. cJ .

[0004] In order to increase H cJ At present, the method of adding heavy rare earth elements RH (mainly Dy) to R-T-B sintered magnets is adopted, but there is a residual magnetic flux density B r (hereinafter sometimes referred to as "B r Therefore, in recent years, the heavy rare earth elements are diffused from the surface to the inside of the R-T-B system sintered magnet, and the heavy rare earth elements are concentrated in the outer shell of the main phase grains, thereby suppressing the B r Lower and get high H cJ method.

[0005] However, due to the limited production of Dy, there are problems such as unstable supply and large price fluctuations. Therefore, it is necessary to use less heavy rare earth elements such as Dy as possible to improve the H of R-T-B sintered magnets. cJ technology.

[0006] Patent Document 1 describes a technique for producing an R2T-B sintered magnet by reducing the B content compared to a general R-T-B sintered magnet and containing one or more metal elements M selected from Al, Ga and Cu. 17 phase, fully ensure that the R2T 17 The transition metal-rich phase (R6T 13 M), thereby suppressing the Dy content and obtaining an R—T—B system sintered magnet with high coercivity.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: International Publication No. 2013 / 008756 Summary of the invention

[0010] Technical problem to be solved by the invention

[0011] Regarding the R-T-B system sintered magnet with a low Dy content as described in Patent Document 1, further improvement of magnetic properties has been sought. The present invention aims to provide a sintered magnet with a low Dy content and high B r and high H cJ A method for producing an R-T-B sintered magnet.

[0012] Technical solutions for solving technical problems

[0013] A first aspect of the present invention is a method for producing an R-T-B based sintered magnet, comprising:

[0014] The step of preparing a raw material for an R-T-B system sintered magnet, wherein the raw material for an R-T-B system sintered magnet contains at least R, B, Ga and T.

[0015] R: 27.0 mass % or more and 35.0 mass % or less, wherein R is a rare earth element and contains at least one selected from the group consisting of Nd, Pr and Ce;

[0016] B: 0.80 mass % or more and 0.93 mass % or less;

[0017] Ga: 0.15 mass % to 1.0 mass %;

[0018] T: 61.5 mass % or more and 70.0 mass % or less (T is Fe or Fe and Co, and 90 mass % or more of T is Fe),

[0019] Furthermore, the R-T-B system sintered magnet raw material satisfies the following formula (1):

[0020] 14[B] / 10.8<[T] / 55.85(1),

[0021] ([B] is the content of B expressed in mass %, [T] is the content of T expressed in mass %); and

[0022] The heat treatment step is to heat treat the RTB based sintered magnet material at a heat treatment temperature of 400° C. to 600° C. for a holding time of 10 seconds to less than 30 minutes.

[0023] A second aspect of the present invention is a method for producing an RTB based sintered magnet, wherein the holding time in the heat treatment step is 10 seconds to 10 minutes.

[0024] A third aspect of the present invention is a method for producing an RTB based sintered magnet, wherein the holding time in the heat treatment step is 10 seconds to 3 minutes.

[0025] Effects of the Invention

[0026] According to the manufacturing method of the present invention, it is possible to provide a semiconductor device having a high B content and suppressing the Dy content. r and high H cJ A method for producing an R-T-B sintered magnet. DETAILED DESCRIPTION

[0027] It is generally known that R-TB sintered magnets are heat treated after sintering. cJ It was previously believed that in order to increase H cJ To reach the maximum value, it is necessary to maintain the heat treatment temperature for at least 1.5 to 3 hours after reaching the optimum heat treatment temperature. cJ ), and heat treatment is performed with the holding time usually set to more than 1.5 hours. r and H cJ Therefore, usually when the holding time is short (for example, 5 minutes), although B r The value of H is high, but cJ Moreover, when the holding time is extended (for example, 3 hours), although H cJ The value of is high, but with H cJ The rise of B r The value of is reduced.

[0028] However, the inventors of the present invention have conducted intensive research and found that the B content is less than R2T as described in Patent Document 1. 14 In an R-TB system sintered magnet containing Ga and a stoichiometric composition ratio of a B compound, it was found, completely unexpectedly, that H can be reduced by heat treatment for an extremely short holding time of less than 30 minutes. cJ In addition, it is also known that if the holding time is extended, B r and H cJ That is, it is found that when the B content is less than R2T 14 In an R-T-B system sintered magnet containing Ga and a stoichiometric composition ratio of a B compound, when the holding time is less than 30 minutes (preferably less than 10 minutes, more preferably less than 3 minutes), B r and H cJBoth show local values ​​or values ​​close to local values. Based on this finding, the inventors of the present invention have completed a method for producing an RTB based sintered magnet according to the present invention.

[0029] Next, the manufacturing method according to the embodiment of the present invention will be described in detail.

[0030] Among them, in the present invention, the material at the stage before the completion of heat treatment under specific conditions (heat treatment at a temperature of 400°C to 600°C for more than 10 seconds and less than 30 minutes) is referred to as "R-T-B system sintered magnet raw material", or simply "sintered magnet raw material". The material obtained after the R-T-B system sintered magnet raw material is subjected to the heat treatment under the above-mentioned specific conditions is referred to as "R-T-B system sintered magnet", or simply "sintered magnet". In other words, in this specification, the material before the heat treatment under the above-mentioned specific conditions and the material undergoing the heat treatment are referred to as "R-T-B system sintered magnet raw material". <Method for producing R-T-B system sintered magnet>

[0031] A method for producing an RTB based sintered magnet according to the present invention will be described.

[0032] The method for producing an RTB system sintered magnet comprises: a step of preparing an RTB system sintered magnet raw material having a predetermined composition; and a heat treatment step of heat-treating the RTB system sintered magnet raw material under specific conditions.

[0033] Next, each process is described.

[0034] (1) Process of preparing raw materials for R-T-B sintered magnets

[0035] The R—T—B system sintered magnet material of the present invention contains at least R, B, Ga and T, and their compositions satisfy the following requirements.

[0036] (R content: 27.0 mass % or more and 35.0 mass % or less)

[0037] R is a rare earth element, and contains at least one selected from Nd, Pr and Ce. The content of R is 27.0 mass % or more and 35.0 mass % or less. If the content of R is less than 27.0 mass %, densification during sintering may become difficult, and if it exceeds 35.0 mass %, the main phase ratio decreases, and a high B r The content of R is preferably 29.5 mass % or more and 33.0 mass % or less. When R is within this range, a higher B r .

[0038] (B content: 0.80 mass % or more and 0.93 mass % or less)

[0039] The content of B in the sintered magnet raw material is 0.80 mass % or more and 0.93 mass % or less and satisfies the formula (1) described below. When the content of B is less than 0.80 mass %, R2T is generated. 17 phase, it may not be possible to obtain a high H cJ When it exceeds 0.93 mass%, the amount of R-T-Ga phase generated is too small, and it may not be possible to obtain a high H cJ The B content is more preferably 0.88 mass % or more and 0.90 mass % or less, which can obtain a higher H cJ Improve the effect.

[0040] (Ga content: 0.15 mass % or more and 1.0 mass % or less)

[0041] The Ga content is 0.15 mass % or more and 1.0 mass % or less. When the Ga content is less than 0.15 mass %, the amount of R-T-Ga phase generated is too small, and R2T 17 phase disappears, and it may not be possible to obtain a high H cJ When it exceeds 1.0 mass%, the main phase ratio decreases due to the presence of unnecessary Ga, and B r The Ga content is preferably 0.2 mass % to 0.8 mass %, and more preferably 0.3 mass % to 0.6 mass %. r and high H cJ .

[0042] (T content: 61.5 mass % or more and 70.0 mass % or less)

[0043] T is Fe or Fe and Co, and 90 mass % or more of T is Fe. By containing Co, the corrosion resistance can be improved. However, when the substitution amount of Co exceeds 10 mass % of T, high B may not be obtained. r The content of T is 61.5 mass % or more and 70.0 mass % or less, and the above formula (1) is satisfied. When the content of T is less than 61.5 mass %, B r It is possible to reduce it significantly.

[0044] The content of T and the content of B in the sintered magnet material satisfy the following formula (1).

[0045] 14[B] / 10.8<[T] / 55.85(1)

[0046] By satisfying the formula (1), the content of B is less than that of a general R-T-B system sintered magnet. 14 No R2T as a soft magnetic phase is generated other than the B phase.17 Phase, becoming a composition where [T] / 55.85 (atomic weight of Fe) is less than 14[B] / 10.8 (atomic weight of B) ([T] is the content of T expressed in mass %). The R-T-B system sintered magnet of the present invention is different from the general R-T-B system sintered magnet, and is limited by formula (1) to [T] / 55.85 being greater than 14[B] / 10.8. However, since the main component of T in the R-T-B system sintered magnet of the present invention is Fe, the atomic weight of Fe is used.

[0047] (Remainder)

[0048] In a preferred embodiment of the sintered magnet raw material, the remainder is T and inevitable impurities. In other words, as long as T satisfies the formula (1), the remainder may be composed of T and inevitable impurities.

[0049] Examples of unavoidable impurities include Cr, Mn, Si, La, Ce, Sm, Ca, and Mg, which are usually contained in Nd-Pr alloys, electrolytic iron, and ferroboron alloys. In addition, examples of unavoidable impurities in the manufacturing process include O (oxygen), N (nitrogen), and C (carbon).

[0050] In another preferred embodiment of the sintered magnet material, any other elements may be contained within the range of achieving the object of the present invention. Examples of other elements that can be selectively contained in this manner are shown below.

[0051] (Cu: more than 0 mass % and 1.0 mass % or less)

[0052] By containing an appropriate amount of Cu, H cJ Further improvement.

[0053] It may contain 1.0 mass % or less of Cu. The content of Cu is preferably 0.05 to 0.50 mass %. When 0.05 to 0.50 mass % of Cu is contained, H cJ Further improvement. (Al: more than 0 mass % and less than 1.0 mass %)

[0054] By containing an appropriate amount of Al, H cJ Further improvement.

[0055] It may contain 1.0 mass % or less of Al. The Al content is preferably 0.05 to 0.50 mass %. When 0.50 mass % or less of Al is contained, H cJFurther improvement. Al can be contained in an amount of 0.05 mass % or more as an inevitable impurity in the manufacturing process, or in an amount of 1.0 mass % or less as the total amount of the amount contained as an inevitable impurity and the amount intentionally added. The Al content is more preferably 0.05 mass % or more and 0.5 mass % or less.

[0056] (Other elements)

[0057] In addition, in addition to the above-mentioned elements, the sintered magnet raw materials may also contain one or more other elements (elements intentionally added except for inevitable impurities). For example, as such elements, a small amount (about 0.1% by mass each) of Ag, Zn, In, Sn, Ti, Ge, Y, H, F, P, S, V, Ni, Mo, Hf, Ta, W, Nb, Zr, etc. may be contained. In addition, the elements listed as the above-mentioned inevitable elements may also be intentionally added. Such elements may contain, for example, 1.0% by mass in total. If this is the case, it is sufficient to obtain a high H cJ R-T-B sintered magnet.

[0058] The R-T-B system sintered magnet raw material having the above composition can be prepared by the following steps (i) to (iii). In other words, the steps of preparing the sintered magnet raw material can include the following steps (i) to (iii). Among them, steps (i) to (iii) are only an example of manufacturing the sintered magnet raw material, and the present invention is not limited thereto.

[0059] The process of preparing the sintered magnet raw material may include a high-temperature heating step (step (iv)) and a diffusion step (step (v)) in addition to steps (i) to (iii).

[0060] (i) Step of preparing alloy powder

[0061] Metals or alloys of the respective elements are prepared so as to have the above-mentioned composition, and the alloy in a flake form is produced by a strip casting method or the like.

[0062] The alloy flakes are hydrogen-pulverized to reduce the size of the coarse pulverized powder to, for example, 1.0 mm or less. Next, the coarse pulverized powder is finely pulverized by a jet mill or the like to obtain a particle size D 50 The finely pulverized powder (alloy powder) has a value (median diameter) of 3 to 7 μm (value obtained by laser diffraction method using air flow dispersion method). In addition, a known lubricant can be added as an auxiliary agent to the coarsely pulverized powder before jet milling, during jet milling, and in the alloy powder after jet milling.

[0063] (ii) Molding process

[0064] The obtained alloy powder is used to perform molding in a magnetic field to obtain a molded body. The molding in a magnetic field may be performed by any known molding method in a magnetic field, including a dry molding method in which dried alloy powder is inserted into a cavity of a mold and then a magnetic field is applied to perform molding, and a wet molding method in which a slurry obtained by dispersing the alloy powder is injected into the cavity of the mold and then a dispersion medium of the slurry is discharged to perform molding.

[0065] (iii) Sintering process

[0066] The R-T-B sintered magnet raw material is obtained by sintering the molded body obtained through the molding process. The molded body can be sintered by a known method (for example, sintering at a sintering temperature of 1000°C to 1090°C for about 1 hour to 10 hours). In addition, in order to prevent oxidation caused by the atmosphere during sintering, it is preferred to sinter in a vacuum atmosphere or in an inert gas. The inert gas is preferably an inert gas such as helium or argon.

[0067] (iv) High temperature heating process

[0068] The sintered magnet raw material obtained by the sintering step is further subjected to a high temperature heating step of heating at a relatively high temperature of 700°C or higher and below the sintering temperature. By performing the high temperature heating step, a sintered magnet raw material having a higher H cJ The heating time in the high temperature heating step is preferably 1.5 hours or more.

[0069] (v) Diffusion process

[0070] The sintered magnet raw material obtained by the sintering process or the sintered magnet raw material after the high-temperature heating process can be further subjected to a diffusion process. The diffusion process can be performed using known diffusion sources and diffusion methods. For example, in Japanese Patent Publication No. 2008-147634, a method is disclosed in which a powder containing Dy, Tb, etc. is present on the surface of a sintered body (the surface of an R-T-B system sintered magnet) and heated at a temperature lower than the sintering temperature, thereby diffusing Dy, Tb, etc. from the above powder to the sintered body. In addition, in WO2018 / 143230, a method is disclosed in which at least a portion of an R-Ga alloy is brought into contact with at least a portion of the surface of an R-T-B system sintered magnet raw material and a first heat treatment is performed at a temperature of 700°C to 950°C to diffuse R and Ga into the interior of the magnet.

[0071] The RTB system sintered magnet after the sintering step (or after the high temperature heating step and / or the diffusion step) may be subjected to a heat treatment step after being machined.

[0072] (2) Heat treatment process

[0073] The sintered magnet raw material obtained by the step of preparing the sintered magnet raw material is subjected to heat treatment for the purpose of improving the magnetic properties. The heat treatment temperature is set to 400°C or higher and 600°C or lower. If the heat treatment temperature is lower than 400°C or higher than 600°C, H cJ and B r As a method for measuring the heat treatment temperature, it is preferred to bring a thermocouple into contact with the R-T-B system sintered magnet raw material in the heat treatment furnace to measure the temperature. In addition, for the sake of simplicity, the correspondence between the temperature in the heat treatment furnace and the temperature of the R-T-B system sintered magnet raw material placed in the heat treatment furnace can be studied in advance by using a thermocouple to simultaneously measure the temperature in the heat treatment furnace and the temperature of another R-T-B system sintered magnet raw material placed in the heat treatment furnace, and based on the correspondence, the temperature of the R-T-B system sintered magnet raw material in the heat treatment furnace is read from the temperature in the heat treatment furnace.

[0074] After the RTB system sintered magnet material reaches the heat treatment temperature, it is maintained at the heat treatment temperature for a period of 10 seconds or more and less than 30 minutes. The manufacturing method according to this embodiment is characterized in that the holding time is extremely short compared with the conventional technology.

[0075] It is known that the H of the R-TB system sintered magnet as the final product can be increased by heat treating the sintered magnet raw material obtained after sintering as described above. cJ In order to make the H cJ To reach the maximum value, it was previously believed that the optimal heat treatment temperature must be maintained for about 1.5 hours to 3 hours or longer. r The maximum value is reached when the holding time is about 10 seconds. When the holding time is further extended, H cJ When the holding time is short, H cJ Therefore, in the prior art, the holding time is set to 1.5 hours or more for heat treatment.

[0076] However, the inventors of the present invention have conducted in-depth research and found that the content of B is less than that of R2T 14 In the R-TB system sintered magnet material containing Ga and a stoichiometric composition ratio of a B compound, a high B and a high B can be obtained by setting the holding time during the heat treatment to a very short time. r and high H cJ It is found that among the R-TB system sintered magnet raw materials having the composition specified in this embodiment, H of the R-TB system sintered magnet cJThe maximum holding time exists in the range of 10 seconds or more and less than 30 minutes. Therefore, in this embodiment, the holding time of the heat treatment is set to 10 seconds or more and less than 30 minutes.

[0077] The holding time is preferably 10 seconds to 25 minutes, more preferably 10 seconds to 10 minutes, more preferably 10 seconds to 5 minutes, and more preferably 10 seconds to 3 minutes. cJ R-T-B sintered magnet.

[0078] In the heat treatment step, in order to suppress oxidation caused by oxygen in the atmosphere, the heat treatment is preferably performed in a vacuum atmosphere or in an inert gas atmosphere. As the inert gas, for example, helium, argon, etc. can be used.

[0079] The obtained sintered magnet may be subjected to mechanical processing such as grinding for the purpose of obtaining the final product shape. In this case, the heat treatment may be performed before or after the mechanical processing. Furthermore, the obtained sintered magnet may be subjected to surface treatment. The surface treatment may be a known surface treatment, such as Al evaporation, Ni electroplating, resin coating, etc.

[0080] The R-T-B sintered magnet thus obtained has a high H cJ and B r The composition of the R-TB system sintered magnet is substantially the same as the composition of the above-mentioned R-TB system sintered magnet raw material.

[0081] Example

[0082] The present invention will be described in further detail using examples, but the present invention is not limited to these examples.

[0083] [Experimental Example 1]

[0084] The elements are weighed so that the composition of the R-T-B system sintered magnet is approximately the composition of No. 1 to No. 3 in Table 1 (for No. 2, it is considered that the composition after diffusion is approximately the composition of No. 2), and cast by strip casting to produce a quenched alloy. The quenched alloy obtained is hydrogen embrittled in a hydrogen pressurized atmosphere, and then subjected to a dehydrogenation treatment of heating to 550°C in a vacuum and cooling to obtain a coarsely pulverized powder. Next, 0.04% by mass of zinc stearate is added to the coarsely pulverized powder as a lubricant relative to 100% by mass of the coarsely pulverized powder. After mixing, it is dry-pulverized in a nitrogen stream using an airflow pulverizer (jet mill) to obtain a particle size D 50 Finely pulverized powder (alloy powder) having a (median diameter) of 4 μm.

[0085] The obtained alloy powder is mixed with a dispersion medium to make a slurry. The solvent uses n-dodecane, which is mixed with methyl octanoate as a lubricant. The concentration of the slurry is set to 70% by mass of alloy powder and 30% by mass of dispersion medium, and the lubricant is 0.16% by mass relative to 100% by mass of alloy powder. The above-mentioned slurry is molded in a magnetic field to obtain a molded body. The magnetic field during molding is a static magnetic field of 0.8MA / m, and the pressure is set to 5MPa. Wherein, as a molding device, a so-called right-angle magnetic field molding device (horizontal magnetic field molding device) in which the magnetic field application direction is orthogonal to the pressurization direction is used.

[0086] The obtained molded body was sintered in vacuum at 1000°C to 1090°C (a temperature that fully densifies the sample by sintering was selected for each sample) for 4 hours and cooled to room temperature, and then kept at 800°C for 2 hours in vacuum, and then rapidly cooled to room temperature to obtain R-TB sintered magnet raw materials (No. 1' to No. 3'). The density of the obtained R-TB sintered magnet raw materials is 7.5Mg / m 3 above.

[0087] Next, the R-TB system sintered magnet raw material of No. 2' is subjected to diffusion treatment. First, a diffusion alloy is prepared. Regarding the diffusion alloy, the raw materials of each element are weighed and melted so that the composition of the diffusion alloy is approximately Pr: 80 mass%, Tb: 10 mass%, Ga: 5 mass%, and Cu: 5 mass%. The alloy is made into a strip or thin sheet by a single roll super-quenching method (melt spinning method). The obtained alloy is crushed in an argon atmosphere using a mortar and then passed through a sieve with a mesh of 425μm to prepare a diffusion alloy (PrTbGaCu alloy). The composition of the obtained diffusion alloy is measured by high-frequency inductively coupled plasma emission spectrometry (ICP-OES), and the result is almost the target composition (Pr: 80 mass%, Tb: 10 mass%, Ga: 5 mass%, Cu: 5 mass%). Next, the above-mentioned diffusion alloy is scattered on the surface (the entire surface) of the R-TB system sintered magnet raw material of No. 2'. The amount of the dispersion was 3.3% by mass relative to 100% by mass of the R-TB system sintered magnet raw material. Then, the diffusion treatment was performed by heating at 900°C for 3 hours in a reduced pressure argon gas controlled at 50 Pa. Thus, the R-TB system sintered magnet raw material (No. 2") after the diffusion process was prepared.

[0088] Next, the RTB sintered magnet materials No. 1', 2", and 3' were heat treated under the conditions shown in Table 2 to obtain RTB sintered magnets. The heat treatment temperature was measured by bringing a thermocouple into contact with the RTB sintered magnet materials in the heat treatment furnace.

[0089] The components of the obtained R-T-B system sintered magnet are shown in Table 1. The components in Table 1 were measured using high-frequency inductively coupled plasma emission spectrometry (ICP-OES). In addition, the satisfaction of formula (1) is shown in Table 1. "○" means that the formula (1) is satisfied, and "×" means that the formula (1) is not satisfied. In addition, the B of the obtained R-T-B system sintered magnet is r and H cJ The values ​​of B are shown in Table 2. r and H cJ The values ​​of B were measured as follows: R-T-B sintered magnets were machined into samples of 7 mm × 7 mm × 7 mm, and the B values ​​were measured using a BH tracer. r and H cJ The value of .

[0090] In Table 2, the values ​​of magnetic properties judged to be high are underlined. r Satisfy 1.40(T) or above, and H cJ When the voltage is above 1500 (kA / m), r Value and H cJ The value is underlined on both sides. r and H cJ If either value does not meet the above criteria, neither value is underlined.

[0091] [Table 1]

[0092]

[0093] [Table 2]

[0094]

[0095] As for the examples of the present invention and the comparative examples shown in Table 2, it can be seen from the comparison between the five sintered magnets of No. 1, the five sintered magnets of No. 2, the two sintered magnets of No. 4, the two sintered magnets of No. 5, and the two sintered magnets of No. 6 that the holding time during the heat treatment is within the range of the present invention, B r and H cJ Both show the maximum value or the value close to the maximum value that can be obtained with this composition. In contrast, No. 3 (the amount of B and the formula (1) are outside the range) of the composition of the R-T-B system sintered magnet outside the composition range of the present invention, H cJ On the other hand, for No.3 with the same composition, when the holding time is extended (180 minutes), although H cJ Rising, but accompanied by H cJ The rise of Br In addition, as shown in Table 2, in order to obtain a higher B r and high H cJ The holding time during the heat treatment is preferably 10 minutes or less, more preferably 5 minutes or less, and even more preferably 3 minutes or less.

Claims

1. A method for producing an R-T-B system sintered magnet, characterized in that: include: The step of preparing a raw material for an R-T-B system sintered magnet, wherein the raw material for an R-T-B system sintered magnet contains at least R, B, Ga and T. R: 27.0 mass % or more and 35.0 mass % or less, wherein R is a rare earth element and contains at least one selected from the group consisting of Nd, Pr and Ce; B: 0.80 mass % or more and 0.93 mass % or less; Ga: 0.15 mass % to 1.0 mass %; T: 61.5 mass % or more and 70.0 mass % or less, wherein T is Fe or Fe and Co, and 90 mass % or more of T is Fe, Furthermore, the R-T-B system sintered magnet raw material satisfies the following formula (1): 14[B] / 10.8<[T] / 55.85 (1) wherein [B] is the content of B expressed in mass %, and [T] is the content of T expressed in mass %; and The heat treatment step is to heat treat the RTB based sintered magnet material at a heat treatment temperature of 400° C. to 600° C. for a holding time of 6 minutes to less than 30 minutes.

2. The method for producing an R-T-B system sintered magnet according to claim 1, wherein: The holding time in the heat treatment step is 6 minutes to 10 minutes.

3. The method for producing an R-T-B system sintered magnet according to claim 1 or 2, wherein: The process of preparing the raw material of the R-T-B system sintered magnet comprises: A step of preparing an alloy powder having the composition of claim 1, The step includes a step of molding the alloy powder in a magnetic field to obtain a molded body, and a step of sintering the molded body to obtain a sintered magnet material.

4. The method for producing an R-T-B system sintered magnet according to claim 3, wherein: The step of preparing the raw material of the R-T-B system sintered magnet also includes: A high temperature heating step of heating the sintered magnet material obtained in the step of obtaining the sintered magnet material at a temperature of 700° C. or higher and not higher than a sintering temperature.

5. The method for producing an R-T-B system sintered magnet according to claim 4, wherein: The step of preparing the raw material of the R-T-B system sintered magnet also includes: A diffusion step is performed to diffuse the sintered magnet material after the high temperature heating step.

6. A method for producing an R-T-B system sintered magnet, characterized in that: include: The step of preparing a raw material for an R-T-B system sintered magnet, wherein the raw material for an R-T-B system sintered magnet contains at least R, B, Ga and T. R: 27.0 mass % or more and 35.0 mass % or less, wherein R is a rare earth element and contains at least one selected from the group consisting of Nd, Pr and Ce; B: 0.80 mass % or more and 0.93 mass % or less; Ga: 0.15 mass % to 1.0 mass %; T: 61.5 mass % or more and 70.0 mass % or less, wherein T is Fe or Fe and Co, and 90 mass % or more of T is Fe, Furthermore, the R-T-B system sintered magnet raw material satisfies the following formula (1): 14[B] / 10.8<[T] / 55.85 (1) wherein [B] is the content of B expressed in mass %, and [T] is the content of T expressed in mass %; and The heat treatment step is to heat treat the RTB system sintered magnet raw material at a heat treatment temperature of 400° C. to 600° C. for a holding time of 3 minutes to less than 30 minutes. The process of preparing the raw material of the R-T-B system sintered magnet comprises: A step of preparing an alloy powder having the above-described composition, A molding process of using the alloy powder to mold in a magnetic field to obtain a molded body, a step of sintering the molded body to obtain a sintered magnet raw material, A high temperature heating step of heating the sintered magnet material obtained in the step of obtaining the sintered magnet material at a temperature of 700° C. or higher and below the sintering temperature, and a diffusion step of subjecting the sintered magnet material subjected to the high temperature heating step to diffusion treatment.

7. The method for producing an R-T-B system sintered magnet according to claim 6, wherein: The holding time in the heat treatment step is 3 minutes to 10 minutes.

Citation Information

Patent Citations

  • Manufacturing method of rare earth permanent magnet

    JP2008147634A

  • Alloy for r-t-b-based rare earth sintered magnet, process for producing alloy for r-t-b-based rare earth sintered magnet, alloy material for r-t-b-based rare earth sintered magnet, r-t-b-based rare earth sintered magnet, process for producing r-t-b-based rare earth sintered magnet, and motor

    WO2013008756A1

  • Method for producing r-t-b sintered magnet

    WO2018143230A1

  • Method for manufacturing r-t-b based sintered magnet

    JP2018018911A